Shaping local identity through public health: the role of social integration among new-generation rural migrants in urban China - Youhua Wang; Chunhong Xiao; Yushuang Zheng; Zhonglin Liu; Zhihao Jiang; Yue Li (BMC Public Health)
Abstract Background The health of migrant populations has become a critical public health concern amid China’s rapid urbanization, especially within the framework of the “Healthy China” initiative aimed at reducing health disparities. While existing research has extensively examined the challenges rural migrants face regarding employment, housing, and access to services, the specific role of public health services in shaping local identity remains underexplored. This study investigates how public health influences local identity among new-generation rural migrants and examines the mediating role of social integration in this relationship, addressing a significant gap in the migration and public health literature. Methods Utilizing data from 56,014 new-generation rural migrants, this study employed ordinary least squares (OLS) and logistic regression models to assess the impact of three public health indicators—public health awareness, health records, and health education—on social integration and local identity. The Karlson-Holm-Breen (KHB) method was applied to evaluate mediation effects within a counterfactual framework, adjusting for demographic, socioeconomic, and migration-related variables. Results All three public health variables had statistically significant and positive effects on both social integration and local identity (p < 0.001). Public health awareness exhibited the strongest association with local identity, followed by health records and health education. KHB decomposition revealed that social integration mediated approximately 30% of the total effect of public health on local identity. Specifically, the mediating effect accounted for 30.22% for public health awareness, 33.12% for health records, and 29.43% for health education. Despite uniformly significant effects, the degree of mediation varied only slightly, indicating a stable and robust mediating role of social integration. Conclusions Public health services are positively associated with the development of local identity among new-generation rural migrants, with social integration serving as a critical mediating mechanism. These findings underscore the potential of comprehensive public health strategies not only to meet the health needs of migrant populations but also to promote their social integration. This research provides empirical support for China’s “Healthy China” initiative and offers actionable insights for designing policies aimed at enhancing migrant inclusion through improved public health access and community-based interventions.